The Historically Changing Notion of (Female Bodily) Proportion and Its Relevance to Literature - Yokota-Murakami Takayuki (Perichoresis: The Theological Journal of Emanuel University, 2020)
Futabatei Shimei (1864-1909) was an early modern Japanese novelist, translator, and critic. He wrote what is now generally conceived of as the first Japanese ‘modern’ novel, Drifting Clouds (1887-89). He translated works by Turgenev, Leo Tolstoy, Garshin, Gorky, and others. He also published a number of critical essays, treatises on literary theory, political papers, and so forth. His early translation of Turgenev’s short stories: Aibiki (Rendevous, 1888) and Meguriai (Three Trysts, 1889) were extremely influential on the contemporary literati, who were amazed at the fresh, poetic prose used in stark contrast to the traditional Japanese fiction in the pre-Reformation period. These translations, seen in the light of the present-day readers, were unique in what we might term today ‘foreignizing translation’. Lawrence Venuti in Invisibility of the Translator argues that the ideal of (English) translation has been to conceal itself as a translation, i.e. to present itself as an original text (chap I and passim). In that sense, Futabatei’s translations, scandalously presenting itself as a translation, that is to say, as an alien text, is extremely ‘foreignizing’.